Martensitic organic crystals as soft actuators. Issue 31 (24th July 2019) - Li, Liang; Commins, Patrick; Al-Handawi, Marieh B.; Karothu, Durga Prasad; Halabi, Jad Mahmoud; Schramm, Stefan; Weston, James; Rezgui, Rachid; Naumov, Panče
Abstract : Being capable of rapid and complete structure switching, the martensitic phase transitions in molecular crystals are thought to hold a tremendous potential as thermally driven organic actuators. Abstract : Being capable of rapid and complete structure switching, the martensitic phase transitions in molecular crystals are thought to hold a tremendous potential as thermally driven organic actuators. However, the mechanical engineering parlance in the assessment of their performance is not immediately legible to the chemistry research community that starts to explore these materials, and the unavailability of performance indices has precluded molecular crystals from being considered in the device design process. Here, we demonstrate that an organic martensite, hexamethylbenzene, can be used to perform work that is comparable to that of most actuator classes. Millimeter-size single crystals of this material undergo a transition between two forms by uniaxial expansion at a rate of 6.36(2) mm s −1, exerting force in the range 10–100 mN. The force-to-weight ratio of the crystals is on the order of 10 4 and is superior to that of some living creatures. An actuator performance chart reveals that the performance of this material is close to that of nanomuscles, electrostatic actuators and voice coils, with a strain higher than that of electro/magnetostrictive actuators and ceramic piezoelectrics and stress higher than that of the electroactive polymers, MEMS devices, nanomuscles, voice coils, and some solenoids. Moreover, the crystals of this material are mechanically compliant and can be reversibly bent and shaped to fit the desired application. Altogether, the results point to the untapped potential of molecular crystals as rapid and efficient soft, organic actuators.